An Analysis Of The Phonological Uniqueness In Socio-Culture - Winda Putri Sandara Butar-Butar; Nadiya Fitria; Yani Lubis (Politeknik Kampar, 2023)
This journal aims to analyze how the phonological uniqueness of language in the social environment and its role in life. Throughout the world language is very important in communicating between humans with one another, with our language it will be easy to explore or find information. Indonesia has very diverse tribes and cultures and languages ??so that this uniqueness is very much manifested in the social environment. With the diversity of cultures and the times, the language began to be modified to become more modern, such as the language of hits on social media. A unique language is known as a language that is not rigid and also modern which usually arises from the creativity of people in the social environment. The results of this study discuss various unique languages ??that often find in life. As well as diversity which is the main basis for the uniqueness of language and the role of social media which has benefits in exchanging information (unique language) to all souls on earth. Then, examine the uniqueness of language between animals and humans.